2013
DOI: 10.1186/1471-2164-14-265
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous miRNA and mRNA transcriptome profiling of human myoblasts reveals a novel set of myogenic differentiation-associated miRNAs and their target genes

Abstract: BackgroundmiRNA profiling performed in myogenic cells and biopsies from skeletal muscles has previously identified miRNAs involved in myogenesis.ResultsHere, we have performed miRNA transcriptome profiling in human affinity-purified CD56+ myoblasts induced to differentiate in vitro. In total, we have identified 60 miRNAs differentially expressed during myogenic differentiation. Many were not known for being differentially expressed during myogenic differentiation. Of these, 14 (miR-23b, miR-28, miR-98, miR-103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 117 publications
3
74
2
Order By: Relevance
“…The level of expression of miRNA targets in a system is relevant for increasing the success rate in the target prediction [10]. By selecting just the mRNAs that were overexpressed in the transition in situ to metastatic cells, we take into consideration the specific cellular context allowing a more precise prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of expression of miRNA targets in a system is relevant for increasing the success rate in the target prediction [10]. By selecting just the mRNAs that were overexpressed in the transition in situ to metastatic cells, we take into consideration the specific cellular context allowing a more precise prediction.…”
Section: Discussionmentioning
confidence: 99%
“…To perform microarray data analysis we used R language and the Limma package on Bioconductor software essentially as described in [10]. Data were background corrected using AgiMicroRNA algorithm and normalized between arrays by the quantile method in order to compensate for systematic technical differences between probe affinity and arrays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data shown in Fig. 15a suggest that myostatin propeptide may stimulate myogenesis by upregulating miR-23b, as miR-23b is known as a myogenic miRNA (Dmitriev et al, 2013). The myostatin propeptide also upregulates let-7e, and the let-7 group of miRNAs are known to suppress cell proliferation.…”
Section: Year 4 Addendum (May 2014-november 2014)mentioning
confidence: 95%
“…miR23a, 30b, 98, 101, 148b, 206, 145, 199a and let-7 have in silico-predicted targets that are involved in the insulin signalling pathway), it is difficult to determine which of the suggested miRNAs are false positive and which are the true positive. Data from animal studies, muscular disease models, exercise experiments and ageing research by other groups also support, to various extent, the involvement of miR-206, miR-23a, miR23b, miR-30b and miR-98 in muscle atrophy (Drummond et al 2008, Granjon et al 2009, Jeng et al 2009, McCarthy et al 2009, Williams et al 2009, Nakasa et al 2010, Nielsen et al 2010, Wada et al 2011, Liu et al 2012, Dmitriev et al 2013. Recently, a study analysing the expression of miRNA in different mouse models of muscle atrophy showed that each model has a different signature of miRNA changes and, more importantly, that there is a temporal change in miRNA expression (Soares et al 2014).…”
mentioning
confidence: 95%